Categorial shift and morphological differentiation. (May 2019) - Gaeta, Livio
Abstract: Morphological differentiation is defined as the development of morphological variants which can be considered by speakers to shape the transition to a new, different category. After discussing different cases of morphological differentiation, the paper will focus on the accompanying changes that facilitate the process of category formation. This reflects an active Principle of Maximal Differentiation, which helps speakers distinguish the units belonging to the new categories from the others. Highlights: Morphological differentiation consists in the development of morphological variants. The variants are considered by speakers to shape the transition to a new, different category. A number of accompanying changes aim at easing the process of identification of the new category. They reflect an active Principle of Maximal Differentiation. This helps speakers detect the units belonging to the new categories from the others.